MALE INFERTILITY: ETIOLOGY AND PATHOGENESIS (World Bulletin of Public Health, 2026)
Male infertility is a complex and multifactorial condition that affects approximately half of couples with reproductive problems. The etiology of the disease includes genetic abnormalities, endocrine disorders, inflammatory and infectious processes, anatomical and obstructive disorders, immunological factors, as well as lifestyle and environmental influences. The pathogenesis of male infertility is associated with impaired spermatogenesis, hormonal imbalance, oxidative stress, sperm DNA fragmentation, and immunological damage. Despite advances in molecular genetics and reproductive medicine, a significant proportion of cases remain idiopathic, highlighting the need for further research. This review summarizes current data on the causes and mechanisms of male infertility, emphasizing current concepts, diagnostic challenges, and prospects for clinical and experimental research.
Keywords: Male infertility; etiology of infertility; pathogenesis of infertility